Physicochemical conditions for the stability of manganese-doped nanolayers of gallium arsenide and its iso-electronic analogues - Yu. V. Terenteva; L. V. Fomina; S. A. Beznosyuk (Chimica Techno Acta)
In this paper research of stability of nanolayers of manganese doped materials of AIIIBV and AIIBIVСV2 types holding much promise as spintronic semiconductor compounds is described. The method of non-local density functional has been applied to calculate bonding energies {εij (r)} in atomic pairs for structures of AIIIBV and AIIBIVСV2 types and for MnAs. According to the calculations of internal energy, entropy and free energy of Helmholtz (Т = 298К), in the context of used models, addition of manganese to the arsenide’s AIIIBV and AIIBIVСV2 nanolayers affects its stability in different ways depending on its morphology and substitution mode. However, a critical instability in nanofilm leading to the tendency of growing of a new phase germ may be formed under any manganese concentrations. This leads to deterioration of electrophysical parameters of magnetic semiconductor compounds that is agreed with experimental data.